Identification and cloning of a regulatory gene for nitrogen assimilation in the cyanobacterium Synechococcus sp. strain PCC 7942. - Vega-Palas, M A (1990)
Twenty-seven mutants that were unable to assimilate nitrate were isolated from Synechococcus sp. strain PCC 7942. In addition to mutants that lacked nitrate reductase or nitrite reductase, seven pleiotropic mutants impaired in both reductases, glutamine synthetase, and methylammonium transport were also isolated. One of the pleiotropic mutants was complemented by transformation with a cosmid gene bank from wild-type strain PCC 7942. Three complementing cosmids were isolated, and a 3.1-kilobase-pair DNA fragment that was still able to complement the mutant was identified. The regulatory gene that was cloned (ntcA) appeared to be required for full expression of proteins subject to ammonium repression in Synechococcus sp.